Karakteristik Komunitas Serangga Pengunjung Bunga Pada Beberapa Tanaman Refugia - Wilyus Wilyus; Winarto Winarto; Fuad Nurdiansyah (Jurnal Media Pertanian, 2022)
This study was conducted to determine the characteristics of the insect community of flower visitors on several refugia plants. The research was carried out in the experimental field of the Faculty of Agriculture, Jambi University and the Laboratory of Plant Pests, Faculty of Agriculture, Jambi University. Samples of flower-visiting insects were taken using the yellow pan trap, pitfall trap, and sweep trap. The insects obtained were identified in the Laboratory of the Faculty of Agriculture, Jambi University. Characteristics of insect communities in refugia plants were calculated using the formulas of diversity index, similarity index, dominance index, and similarity index. The results showed that the abundance of species and populations of insects was most commonly found in Zinnia elegans flowers. Most predatory insects were found in Z. elegans flowers, pollinator insects were most abundant in Helianthus annuus flowers, and pollinators were most abundant in Z.  elegans flowers. The characteristics of the insect community in the most stable refugian plant were found in Tagetes erecta flowers. The highest similarity of insect communities was found in Cosmos caudatus flowers and Impatiens balsamina flowers.